الخصائص الهيدرولوجية لحوض وادي الشكاك شرقي محافظة ميسان باستخدام نظم المعلومات الجغرافية *GIS - Faleh Khulaibis Daoud; Prof. Dr. Amal Hadi Al-Jabri (Journal of College of Education, 2024)
The study aims to analyze the hydrological characteristics of Wadi Al-Shakak, east of Maysan Governorate, which is astronomically located between latitudes (11-32° - 20-32°) north and longitudes (22-47° - 28-47°) east. Geographically, it is located in the eastern end.  From Maysan Governorate, with an area of (99.95) km 2, the study focused on the physical and chemical characteristics of the water of the research area valley, through the use of Geographic Information Systems (GIS) programs and laboratory analysis, this study provided a solid detailed geographical database on the basins, as well as planning for investment  Natural resources by government agencies and the people residing in the region and finding solutions to the problems that stand in the way of investing these resources.
Keywords: hydrological characteristics , water basin , waterways network